2003
DOI: 10.1161/01.cir.0000087449.03964.fb
|View full text |Cite
|
Sign up to set email alerts
|

Failure to Prevent Progressive Dilation of Ascending Aorta by Aortic Valve Replacement in Patients With Bicuspid Aortic Valve: Comparison With Tricuspid Aortic Valve

Abstract: Background-Patients with bicuspid aortic valve (BAV) have been frequently complicated with ascending aortic dilation possibly because of hemodynamic burdens by aortic stenosis (AS) or regurgitation (AR) or congenital fragility of the aortic wall. Methods and Results-To clarify if the aortic dilation could be prevented by aortic valve replacement (AVR) in BAV patients, we studied 13 BAV (8 AR dominant, 5 AS dominant) and 14 tricuspid aortic valve (TAV) patients (7 AR, 7 AS) by echocardiography before and after … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
160
2
8

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 195 publications
(179 citation statements)
references
References 30 publications
6
160
2
8
Order By: Relevance
“…Patients with bicuspid aortic valve, the most common congenital heart defect, are at increased risk for ascending aortic dilatation (73). Proteoglycans facilitate collagen assembly and synthesis, a critical process for the development of semilunar valves and ascending aorta (37).…”
Section: Myh6komentioning
confidence: 99%
“…Patients with bicuspid aortic valve, the most common congenital heart defect, are at increased risk for ascending aortic dilatation (73). Proteoglycans facilitate collagen assembly and synthesis, a critical process for the development of semilunar valves and ascending aorta (37).…”
Section: Myh6komentioning
confidence: 99%
“…Потенциальные участки формирования ЛА: область наложения поперечного за-жима, линия шва и места катетеризации аорты, границы анастомозов [4,7]. Пациенты с двустворчатым АК нахо-дятся в группе повышенного риска развития осложнений со стороны аорты, при этом замена АК полностью не ис-ключает возможность прогрессирования дилатации [8,9]. Клиническая картина при этой патологии размыта и может варьировать от бессимптомного течения до лихо-радочных состояний, учитывая частую ассоциацию с ИЭ [1].…”
Section: Discussionunclassified
“…Studies on children (Beroukhim et al, 2006;Warren et al, 2006;Holmes et al, 2007) and adults (Yasuda et al, 2003;Davies et al, 2007;Tadros et al, 2009) have reported significantly faster aortic dilatation in the significantly younger with BAV versus trileaflet aortic valve (Figure). BAV is associated with ascending aortic dilatation and enlargement of the aortic root annulus in as many as half of all individuals (Nkomo et al, 2003;Park et al, 2011).…”
Section: Surgical Treatment Of Bicuspid Aortic Valve With Aortopathymentioning
confidence: 96%